Medicinal plants with antimalarial activities mediated via glycogen synthase kinase-3 beta (GSK3β) inhibition - Hassan, Wan Rozianoor Mohd; Ali, Amatul Hamizah; Basir, Rusliza; Embi, Noor; Mohd Sidek, Hasidah (Malaysian Society of Parasitology and Tropical Medicine, 2022)
Many of the therapeutic effects of plant extracts and bioactive compounds appear related to their immunomodulatory effects and impact on the host immune system. The immune response is desirable to mitigate established infections and, in the case of severe malaria, is a feasible approach to dealing with the overwhelming cytokine response. Glycogen synthase kinase-3 (GSK3), a Ser/Thr kinase that is a central regulator of the cytokine response, is a promising antimalarial drug target. In this review, we discussed our ongoing research projects, which include assessing the antimalarial activities of medicinal plants and their bioactive compounds, immunomodulatory activities mediated by GSK3, and the potential inflammatory pathway involved in malarial infection.